Levels and distribution of tris-(2, 3-dibromopropyl) isocyanurate and hexabromocyclododecanes in surface sediments from the Yellow River Delta wetland of China. Issue 1 (15th January 2017) - Wang, Ling; Zhang, Mengyuan; Lou, Yinghua; Ke, Runhui; Zheng, Minggang
Abstract: The levels and distribution of tris-(2, 3-dibromopropyl) isocyanurate (TBC) and hexabromocyclododecanes (HBCDs) of surface sediments in the Yellow River Delta wetland had been investigated. The concentrations of TBC and ∑ HBCDs ranged from 0.20 to 29.03 ng·g − 1 dw and below limits of detections (LODs) to 20.25 ng·g − 1 dw. The average composition profile of three HBCDs isomers were 10.1%, 6.1% and 83.8% for α-, β- and γ-HBCD, respectively. Moreover, correlation analysis indicated there are similar sources among three isomers and positive correlations between total organic carbon (TOC) content and concentrations of TBC and HBCDs. The mass inventory of TBC, α-, β-, γ-HBCD, ΣHBCDs in surface sediments of Yellow River Delta wetland were estimated about 725.50, 72.76, 44.29, 548.34, 665.39 kg. Therefore, further investigations on potential human health and environmental risk assessments of TBC and HBCDs were needed. Highlights: TBC and HBCDs were detected in surface sediments from The Yellow River Delta wetland of China. Spearman correlation of HBCDs and TBC was analyzed. Positive and not significant correlations were found between TOC content and concentrations of TBC, HBCDs in sediment samples. The mass inventory of TBC and HBCDs in sediments were estimated.